Ultrashort carbon nanotubes with luminescent color centers are bright NIR-II nanoemitters - Nandi, Somen; Gresil, Quentin; Lambert, Benjamin P.; Sebastian, Finn; Settele, Simon; Calaresu, Ivo; Estaun-Panzano, Juan; Lovisotto, Anna; Mazzocco, Claire; Flavel, Benjamin S.; Bezard, Erwan; Groc, Laurent; et al. (ACS nano, 2025)
In the fields of bioimaging, photonics, and quantum science, it is equally crucial to combine high brightness with a nanoscale size in short-wave infrared (SWIR) emitters. However, such nanoemitters are currently lacking. Here, we report that when functionalized with luminescent color centers, ultrashort carbon nanotubes with a length much shorter than 100 nm are surprisingly bright in the near-infrared second-biological window (NIR-II) of the SWIR domain. We discuss the origin of this exceptional brightness based on the uncontrollable presence of quenching defects in dispersed carbon nanotubes. We further investigate the nonlinear photoluminescence behavior of color center-functionalized carbon nanotubes in response to varying excitation conditions, spanning from ensemble measurements to single-nanotube experiments. We discuss how this behavior influences the determination of their photoluminescence quantum yields, which can reach values as high as 20% for ultrashort ones detected at the single-nanotube level. Notably, the corresponding NIR-II brightness exceeds that of well-known visible emitters, including quantum dots. After rendering them biocompatible, we demonstrate point-spread function engineering and high-resolution, 3-dimensional single-particle tracking using these bright ultrashort carbon nanotubes allowing nanoscale imaging in the NIR-II window within thick brain tissue.
Gesehen am 04.11.2025